Partisipasi Masyarakat Dalam Pelaksanaan Musyawarah Perencanaan Pembangunan (Musrembang) Desa - Darin Darin; Usman Moonti; Sri Indriyani S. Dai (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
The research aims to determine the community participation in the implemention of Development Planning Forum (Musrembang) in Guali Village, Kusambi Subdistrict, Muna Barat Regency. The type of research used is qualitative descriptive research, where the data collection techniques used observation, interview, and documentation study, and this research involves several informants. The research findings indicate that the community does partipacipate in the implementation of the Development Planning Forum (Musrembang) of Guali Village, both trough suggestion and energy contributed by the community. For instance, the community takes a part through their energy to construct village farming road as proposed in the forum regardless of a condition where not all of them involve in the implementation of Development Planning Forum (Musrembang).